Flow Cytometric Quantification of Fatty Acid Uptake byMycobacterium tuberculosis in Macrophages - Nazarova, Evgeniya V. (Bio Protoc, 2018)
Mycobacterium tuberculosis (Mtb) has evolved to assimilate fatty acids from its host. However, until recently, there was no reliable way to quantify fatty acid uptake by the bacteria during host cell infection. Here we describe a new method to quantify fatty acid uptake by intracellular bacilli. We infect macrophages with Mtb constitutively expressing mCherry and then metabolically label them with Bodipy-palmitate. Following the labeling procedure, we isolate Mtb-containing phagosomes on a sucrose cushion and disrupt the phagosomes with detergent. After extensive washes, the isolated bacteria are analyzed by flow cytometry to determine the level of Bodipy-palmitate signal associated with the bacteria. Using a Mtb mutant strain defective in fatty acid uptake in liquid culture we determined that this mutant assimilated 10-fold less Bodipy-palmitate than the wild type strain during infection in macrophages. This quantitative method of fatty acid uptake can be used to further identify pathways involved in lipid uptake by intracellular Mtb and possibly other bacteria.